THE EFFECT OF PHARMACIST INTERVENTION THROUGH TELEPHARMACY SERVICES ON COMPLIANCE AND FASTING BLOOD SUGAR LEVELS IN DIABETES MELLITUS TYPE 2 PATIENTS AT NATALIA FARMA PHARMACY - Dharmawan, Nancy Natalia; Virginia, Dita Maria; Priyatni, Nunung (Jurnal Farmasi Sains dan Praktis, 2025)
Diabetes Mellitus is a disease that cannot be cured; thus, it requires high compliance to control blood sugar levels and prevent complications. Telepharmacy can help improve Type 2 Diabetes Mellitus Patients (T2DM) compliance by providing information and education about the disease, medications, and how to use the medication appropriately. The purpose of this study is to analyze the level of compliance and the fasting blood sugar levels of T2DM patients after receiving telepharmacy services by pharmacists at Natalia Farma Pharmacy. This study uses a cohort design with a purposive sampling technique. The research population is the diabetic patients at Natalia Farma Pharmacy in Ende Regency, with a sample size of 60 subjects. In this study, there were two groups observed, namely the intervention and control groups. The intervention group received additional telepharmacy services through WhatsApp for 3 months, including education, drug therapy monitoring, and reminders to take medication. Patient compliance and blood sugar measurement were carried out before and after administering the intervention. The data obtained were then analyzed using SPSS with the t-test. The results showed that telepharmacy affected both patient compliance and fasting blood sugar level, with p-values of 0.002 and 0.009, respectively. Therefore, the existence of telepharmacy intervention can significantly enhance patient compliance and help to control fasting blood sugar levels in T2DM patients at Natalia Farma Ende Pharmacy